Intravitreal Melphalan Chemotherapy for Vitreous Seeds in Retinoblastoma - Yacoub A. Yousef; Amal M. Noureldin; Iyad Sultan; Rasha Deebajah; Maysa Al-Hussaini; Munir Shawagfeh; Mustafa Mehyar; Mona Mohammad; Imad Jaradat; Ibrahim AlNawaiseh (Journal of Ophthalmology)
Objective. To evaluate our experience with intravitreal melphalan chemotherapy as a second-line regimen for RB patients with refractory or recurrent vitreous seeds. Methods. A retrospective case series of 16 eyes from 16 patients with intraocular RB who received intravitreal melphalan chemotherapy using the antireflux injection technique. Data included demographics, stage at diagnosis, treatment modalities, side effects, eye salvage, and survival. Results. The total number of injections was 64 (median, 3 injections per eye; range, 3–8), and the median age at time of injection was 22 months (range, 9–63 months). Nine (56%) patients were males, and 13 (81%) patients had bilateral RB. Complete response was seen in 13 (81%) eyes: in 9 (100%) eyes with focal vitreous seeds and in 4 (57%) eyes with diffuse vitreous seeds (P=0.062). At a median follow-up of 18 months (range, 6–48 months), the eye salvage rate was 81%, local retinal toxicity confined to the site of injection was seen in 2/3 of the eyes, 2 (12%) eyes had cataract, and none of the patients had orbital recurrence and distant metastasis or was dead. Conclusion. Intravitreal melphalan is a promising modality for treatment of vitreous seeds, and the dose of 20–30 μg of melphalan sounds to be safe and effective for refractory and recurrent vitreous seeds.